COMPARISON OF EFFICIENCY AND CARBON EMISSIONS OF FILAMENT ELECTRIC STOVES AND INDUCTION ELECTRIC STOVES - Tiandho, Yuant; Afriani, Fitri (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2021)
Issues related to energy sustainability and carbon emission reduction are continuously being concerned by the Government of the Republic of Indonesia. Various efforts and programs have been launched to achieve targets of the related issues. As known that energy use for cooking by the household is continuously increasing in relation to population growth that will of course increase in energy need which relates to the sustainability of presence energy and carbon emission.Â Accordingly, the LPG stove conversion program to an electric stove was introduced in order to achieve the target to solve such issues. This paper compared of efficiency and carbon emissions of both electric filament stoves and induction stoves. The result indicated that the induction stove has better efficiency compared with the electric stove. The study also was proved that the carbon emissions for both types of stoves were relatively low in comparison with LPG stoves. However, the enormous operational power of the induction stove is still a challenge that must be resolved to achieve the target of energy sustainability in Indonesia.